The curricula for psychology majors in five universities of greater Manila and a proposed program for psychology majors in Thailand - Onanong Yenuthog 1943- (s.n.], 1968)
The curricula for psychology majors in the Ateneo de Manila University, the Far Eastern University, the Philippine Women's University, the University of Santo Tomas, and the University of the Philippines are gathered, interpreted, and analyzed. The underlying principles of the curricula for psychology majors are determined. Furthermore, the study proposed a program for psychology and a set of guidelines for effective implementation of the proposed program.